2020
DOI: 10.3390/ma13112478
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electrochemical Process for Desulfurization in the CaO-SiO2-Al2O3 System

Abstract: The effect of electric potential on the sulfide capacity of the CaO-SiO2-Al2O3 system was evaluated by applying voltages in the range of −1.5 to 1.5 V at 1823 K in a C/CO gas equilibrium. When the cathodic potential (−1.5 to 0 V) was applied, it was confirmed that the sulfur partition ratio increased based on the electrochemical reaction of sulfur (S + 2e− = S2−). However, the reversibility of the electrochemical resulfurization reaction (S2− = S + 2e−) in slag was not established in the reverse (anodic) poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cord steel wire is widely used in industry because of its excellent performance, a d is used in the bridge industry to make the main load-bearing component cables, in the tire industry to make tire skeletons [1,2] and in the photovoltaic industry for cutting silicon wafers [3,4]. The diameter of steel cord is 80~200 µm, which is for the main skeleton of tires, and the diameter of cutting steel wire is 50~80 µm, which is mainly used for cutting precious materials such as solar silicon wafers, gems and aviation semiconductors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cord steel wire is widely used in industry because of its excellent performance, a d is used in the bridge industry to make the main load-bearing component cables, in the tire industry to make tire skeletons [1,2] and in the photovoltaic industry for cutting silicon wafers [3,4]. The diameter of steel cord is 80~200 µm, which is for the main skeleton of tires, and the diameter of cutting steel wire is 50~80 µm, which is mainly used for cutting precious materials such as solar silicon wafers, gems and aviation semiconductors [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cathodic polarization of the melt interface between molten Cu and molten SiO 2 -CaO-Al 2 O 3 can promote the dissolution of S present in Cu into slag. [32][33][34] In contrast, few studies have concentrated on the phenomenon of a positively induced anode reaction at the molten iron-slag interface. The basic concept of this study is to promote the dissolution of Cu in molten Fe into molten slag via electrolysis.…”
mentioning
confidence: 99%
“…Reports regarding the recent advances in electrochemical processes for the destruction of pollutants were also pointed out for potential anodic electro-desulfurization [ 5 ], sequenced electrooxidation–plasma treatment [ 6 ], electrochemical chloride removal [ 7 ], and electrodisinfection [ 8 ]. By applying anodic potentials, the sulfur partition ratio was determined, allowing the proposal of an anodic electro-desulfurization mechanism, which will allow further advances on pyrometallurgy processes [ 5 ].…”
mentioning
confidence: 99%
“…Reports regarding the recent advances in electrochemical processes for the destruction of pollutants were also pointed out for potential anodic electro-desulfurization [ 5 ], sequenced electrooxidation–plasma treatment [ 6 ], electrochemical chloride removal [ 7 ], and electrodisinfection [ 8 ]. By applying anodic potentials, the sulfur partition ratio was determined, allowing the proposal of an anodic electro-desulfurization mechanism, which will allow further advances on pyrometallurgy processes [ 5 ]. Meanwhile, important benefits could be achieved by using electrochemical oxidation as an alternative to removing azo dyes [ 6 ] and chloride [ 7 ] from different water matrices in order to promote advantages in the food processing industry and concrete construction sectors, respectively.…”
mentioning
confidence: 99%